Microstructural characterization of the protective oxide scale forming on Ni–25Cr–xMn (x = 0.5, 1 and 1.5% wt) in a 200 Pa O2 environment at 1050 °C. (15th March 2020) - Perez, T.; Ghanbaja, J.; Mathieu, S.; Latu-Romain, L.; Vilasi, M.; Wouters, Y.
Abstract: To clarify the influence of manganese on the oxidation behavior of Ni–Cr alloys, high resolution transmission electron microscopy was used to examine the microstructure and chemistry of oxide scales forming at 1050 °C on Ni–25Cr–xMn ( x  = 0.5, 1 and 1.5% wt) in 200 Pa O2 . The scales consisted of two layers of chromia and one layer of spinel Mn1+x Cr2-x O4 . The internal layer exhibited an equiaxed grain structure, whereas columnar grains developed in the outer layer. The results demonstrated that the spinel composition at the chromia-spinel interface was similar regardless of the manganese concentration. Graphical abstract: Image, graphical abstract